An Educational Software Package for Power Systems Analysis and Operation - Yalcinoz, T. (International journal of electrical engineering & education, 2005)
This paper presents a software package developed in Matlab for teaching power systems analysis and operation. The software package is used to support and enhance power engineering education at both undergraduate and postgraduate levels. The application programs in this package include fault analysis, load flow analysis, transient stability, economic dispatch, unit commitment and load forecasting. All modules of the package are independent of each other. The students or researchers can make copies of the software to study and can modify any module of the package.